Fatigue properties of AL/AL-MG alloy laminated materials for the applications to railway tank cars. (May 2019) - Yang, Guangxue; Li, Shuang; Fu, Delong
Highlights: The stress-cycle curve with a survival rate of 97.7% was obtained. The fatigue failure of the laminated plate was determined. The fatigue life of the tank body was calculated based on Miner's linear cumulative damage theory. Abstract: In this study, Al/Al-Mg alloy laminated plates were developed, and such composite materials are applied in a 70 t tank car for transporting concentrated nitric acids. The fatigue tests of the base materials and the lap-welded joint of the Al/Al-Mg alloy laminated plate were conducted, and the stress-cycle (S-N) curve with a survival rate of 97.7% was obtained. The fatigue failure mode was analyzed, and its fracture mechanism of the laminated plates was determined. Furthmore, the mechanical behavior of Al/Al-Mg alloy laminated plate was investigated using the finite element analysis (FEA). Based on the load spectrum of 100 t tank car described in the Association of American Railroads (AAR) standard, in conjunction with the S-N curve of the base materials and the lap-welded joints, the fatigue life of the 70 t tank body was calculated based on the Miner's linear accumulative damage theory. The results showed that the 70 t tank car constructed with such materials can meet the safety requirements of operating for 2.5 million km.